(3OejI GdbUQ hYUQI Cgd GdYUQs - (3Ydj Hf GdMSf Hf Ydj Hf CHj GdWjH GdHGNQRj, CHh GdMSf, J (B467 (3g` s; (3GdKYGdHj , CHh efUhQ YHO Gdedc Hf eMeO Hf ESeGYjd GdfjSCHhQj GdKYGdHj, CHh efUhQ GdKYGdHj,J (B429 (3g` s
(3ChdgG (B:s
(3CMeO Gddg Ydi eG CSHZ ef CPjGd CaVGdg s
(3GfXQ GdbSe GdKGfi HQbe (B661s
(3LYdgG PjdkG Ydi (B" (3jJjeI GdOgQ (B" (3ddKYGdHis
(3fSNI KGdKIs
(3JHUQI GdYfhGf (B:s
(3JPjjds
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs